Socio-Professional Integration and Organisational Stress - Nicoleta CRISTACHE; Ancuța-Loredana CĂRĂUȘ (Revista de Management Comparat International, 2024)
In the organisational environment, stress is a pervasive reality that affects both experienced employees, as well as those starting out in a new company. As organisations face increasingly complex demands and fast-paced work schedules, managing stress becomes a crucial challenge to maintaining employee performance and health. In this context, the professional integration of new employees becomes a particularly sensitive issue, as they face multiple challenges and pressure that can influence their journey within the organisation. Organisational stress and professional integration of new employees are interlinked issues, that require special attention from modern organisations. By providing adequate support, effective communication and personal development programmes, organisations can help create a healthy and productive work environment, in which new employees can successfully integrate and achieve their full potential.